The Ultimate Stakeholder Concept - Mustika Widowati; Sri Hartono; Atif Windawati (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Strategy formulation is an important initial process because it is at this stage that the vision and mission of the organization are determined. Vision and mission contain values and philosophies to be disseminated to all stakeholders as the basis for achieving goals. Stakeholder theory explains the importance of accommodating stakeholder interests in achieving superior company performance, not just accommodating the interests of stockholders. This theory tries to overcome the weakness of stockholder theory which only accommodates the interests of shareholders. New Stakeholder Theory, which also tries to minimize the shortcomings of stakeholder theory, includes several stakeholder components whose interests need to be accommodated but have not been discussed in stakeholder theory. But again that the New Stakeholder Theory is also not yet complete to accommodate the existing weaknesses. The weakness of stakeholders and the new stakeholder theory is that it focuses on interested parties with the basis of transactional relationships in the mere tangible dimension. When the company operates by applying Stakeholder and New Stakeholder Theory, there are still fundamental problems. Weaknesses and some cases occur due to the incompleteness of Stakeholder and New Stakeholder Theory to accommodate stakeholders that are more comprehensive with tangible and intangible dimensions, direct and indirect. By reviewing the literature with meta-analysis, this article will offer the concept of the ultimate stakeholder. The ultimate stakeholder is a concept that places God as the main stakeholder for the organization, God as the central stakeholder of all activities and organizational goals, so that this concept has dimensions of the world hereafter. This concept is expected to be a complete concept to answer the incompleteness of the previous stakeholder theory. This concept is expected to be a plenary concept to answer the incompleteness of previous stakeholder theory and can be used as a basis for formulating the values of the organization's vision and mission in strategy formulation.